O discurso do silêncio: reflexões sobre processos de abstração na produção de desenhos de árvores - Cordeiro, Carlos Henrique Gomes Machado (2014)
The Speech of the Silence: reflections on abstraction processes in the production of drawings of trees is a Poetical Visual research which has as study object the personal production of drawings trees pictures. From works made in studio, I make reflections about creation processes and finalized drawings. A part of the studied works was previously produced and another part was made for this research. Among the latest production, I emphasize the series Trees in Dilution and the drawing Arboreal Vertical Space Progression. Through them I discuss technical processes as well as decisions in the procedures that determined major changes in the creation process. Among the proceedings, I discuss about paint dilution, graphic synthesis, the choice of trees without leaves that arises from my mental repertoire of images, empty spaces, aesthetic experience, composition in parts, therefore, issues which consider the abstraction as the process that must be deeply investigated. In order to build my reflections, I use abstraction processes as the guiding of the research, searching in the Phenomenology the procedures to analyze and understand my practice as drawer. I also resort to History and to Art Criticism to make connections between my production and the works of other artists, with which I realize poetic convergences, as Cézanne, Braque, Mondrian, with regard to the abstractions of the form; Malevich and Opalka, regarding to abstraction of the visible ; and Brancusi and Fontana, who are related to the spatial expansion, towards the real space.